MARRIAGE AND FAMILY ISSUES IN CHINA IN THE CONTEXT OF MODERNISATION - Aldabek, Н.Ә.; Turgenbay, А.А.; Assyl, М.Б. (Journal of Oriental Studies, 2024)
The modernization process in China, marked by swift urbanization and economic growth, has brought about significant changes in the dynamics of marriage and family. One of the issues facing the family and marital institutions today is their global status. The fact that the family is a key social institution and that changes to it directly affect the nation's socioeconomic development determines the significance and applicability of research on family and marriage issues. The article's main purpose is to analyze, using a variety of sources, how modernization and the emergence of marital and family issues in China relate to one another within an economic, social, and cultural framework. Using a micro- and macro-level family research methodology, this article provides a comprehensive examination of the challenges and opportunities shaping the landscape of family and marriage in contemporary China, from the impact of urbanization on family structure to the evolving role of women. The article examines the family crisis from a theoretical and methodological standpoint and describes the opportunities and challenges facing Chinese marriage and family life. The role of the government in the formation of the Chinese family and the main functions of the family in providing social support are also discussed. As a result of the study, it can be clearly observed that the rapid pace of modernization and demographic processes have created a so-called 'transitional' family in China, in which new trends coexist with old traditions. Keywords: China, Confucianism, family and marriage, crisis, modernization.